1998
DOI: 10.1139/f98-060
|View full text |Cite
|
Sign up to set email alerts
|

A process for developing and evaluating indices of fish assemblage integrity

Abstract: We describe a general process for developing an index of fish assemblage integrity, using the Willamette Valley of Oregon, U.S.A., as an example. Such an index is useful for assessing the effects of humans on entire fish assemblages, and the general process can be applied to any biological assemblage and any region. First, a reference condition was determined from historical information, and then candidate metrics of ecological importance were listed. The variability of the candidate metrics in time and space … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(104 citation statements)
references
References 10 publications
2
97
0
5
Order By: Relevance
“…Likely, reduced within-site variability of species metrics (noise), increased among-site variability (signal), or both provided stronger correlations between predictor variables and FQIs than for SQIs. Hughes et al (1998) and Mebane et al (2003) reported that their IBIs had greater among-site versus within-site variability (signal/noise) than the metrics forming them. But Hughes et al (2004) and Whittier et al (Lyons et al 1996;Mundahl and Simon 1999;Ferreira et al 2007;Whittier et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likely, reduced within-site variability of species metrics (noise), increased among-site variability (signal), or both provided stronger correlations between predictor variables and FQIs than for SQIs. Hughes et al (1998) and Mebane et al (2003) reported that their IBIs had greater among-site versus within-site variability (signal/noise) than the metrics forming them. But Hughes et al (2004) and Whittier et al (Lyons et al 1996;Mundahl and Simon 1999;Ferreira et al 2007;Whittier et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Also, Hickman (2000) proposed a sportfishing [Article] index for reservoir populations, but his index uses rank scores of 5, 10, or 15 for each of four qualitative population characteristics (angler quantity and quality, population quantity and quality), while each of the five components of the population quality characteristic was scored 1, 2, or 3. Such scoring increases the variance of indices as compared with continuous metric and index scoring (Hughes et al 1998;Pont et al 2006).…”
mentioning
confidence: 99%
“…by Suter, 1993), although strong counter arguments have been also presented by others (e.g. Simon and Lyons, 1995;Karr and Chu, 1997;Hughes et al, 1998).…”
Section: Index Of Biotic Integritymentioning
confidence: 86%
“…Therefore, it is of paramount importance to rely on the widest base of testers and collaborators when developing a multimetric index. Even when a multimetric index has been correctly developed (see, for instance, Hughes et al, 1998), its ability to measure environmental perturbations depends on the right combination of metrics that are taken into account. Of course, there are no general rules that can help in selecting proper metrics, but usually the latter are chosen on the basis of their presumed general ecological relevance or because of their responsiveness to specific perturbations (e.g.…”
Section: Multimetric Indicesmentioning
confidence: 99%
“…This visual analysis allowed the first selection of appropriate metrics for each zone, i.e., those metrics that separate different pressure classes. Out of these relevant metrics we indicated those with a high contribution to the variation (F1 or F2 > ±0.55) using a principal component analysis (PCA) with the log transformed metric values (log(x + 1)) (Hughes et al, 1998). From these we tested for redundant metrics by a Pearson correlation (McCormick et al, 2001: r > 0.75, p < 0.05).…”
Section: Validationmentioning
confidence: 99%